Dispositioned intimacy. Issue 2 (1st September 2013) - Grant, Stuart
This article addresses fundamental issues raised by a site-specific performance research project conducted by two dancers on rush hour trains and station platforms. Emerging from this moving, fleeting environment, characterized by a placiality and temporality of passingness, this project highlights questions of relationships between intimacy, time, place and movement. These questions are addressed using Martin Buber's philosophy of the primacy of the I–You relation and Edward S. Casey's schema of the co-constitution of place and self through the body. Although the rush hour train is a very specific and limited environment, the precariousness of its inhabitation serves to reveal something of the basic processes by which emplacement and intimacy take hold. Site-based performance generally explores place in its endurance and rootedness. These performances in trains reveal place in its slow tenuousness rather than in its apparent obduracy.